iSpring on English Language Teaching and Learning: A Literature Review - Prativi Khilyatul Auliya (DIDAKTIKA, 2024)
iSpring is one of various software which is benefit in English language teaching and learning. There are numerous researches that bring up the use of iSpring to support the material and quiz development. This research aims at providing comprehensive literature review about iSpring in English language teaching and learning. This research’s objectives are investigating; 1) the roles of iSpring in English language teaching and learning and 2) the effectiveness of iSpring in English language teaching and learning. Qualitative research method with library research approach was used in this research. The data consists of 3 theses, 4 conference proceedings, 5 journal articles that taken mostly from Google Scholar. The data then analysed using content analysis to match the objective of this research. The findings showed that iSpring has several important roles for English language teaching and learning such as; making English teaching and learning activities becomes easier; helping students to learn English language; creating interest, motivation, confident, concentration, and independence for students in English learning; supporting all types of learning styles and various level of students in English learning; providing effective English teaching and learning activities; and also accommodating various English teaching methods. Besides that, this research also showed that iSpring was effective for foreign language distance learning, improving students’ independence on self-evaluation, improving receptive skill, and productive skills as well. Therefore, iSpring is suitable to be used in education, especially to support the English language teaching and learning.